Neutronics performance improvement based on the small lead-based fast reactor SLBR-50 - Zhao, Chen; Lou, Lei; Zhang, Bin; Zhou, Bingyan; Wang, Lianjie; Peng, Xingjie (Frontiers in Energy Research, 2022)
The design of high-performance lead-based fast reactors (LFRs) has become a hotspot in the advanced reactor system. This study evaluates the neutronics performance improvement based on the small LFR SLBR-50. Parameter sensitivity analyses are conducted, including height-to-diameter ratio (H/D), reflector assembly arrangement, and pitch-to-diameter ratio in fuel assembly, fuel material, and fuel enrichment partitioning. Numerical results of eigenvalue in burnup procedure, assembly power distribution, and energy spectrum are analyzed using the Monte-Carlo code RMC. Our findings indicate that the fuel material, fuel partitioning, and H/D are the three most important factors in LFR design. The neutronics performance analyses will assist in LFR design.